Therapeutic Potential of Dragea volubilis Leaf Extract against Scopolamine-induced Memory Impairment in Young and Aged Mice - Sharma, Amit; Gill, Naresh (International Journal of Pharmaceutical Investigation)
Background: Treating neurological disorders is still a major challenge, especially diseases like alzheimer's. Dragea volubilis is a wonder herb with many pharmacological activities like neuroprotective, antioxidant, anti-tumor, and anti-inflammatory. Dragea volubilis is synonymously known as Wattakaka volubilis. Chemical exploration of Dragea volubilis has yielded polyoxypregnane glycosides. Objectives: This study focused to explore the cognition-enhancing and neuroprotective functions of chloroform extract of Dragea volubilis in young and old mice in interoceptive and exteroceptive models. Materials and Methods: The chloroform extract of Dragea volubilis (CDV) was prepared by the soxhlation method. The antioxidant, anticholinesterase, and behavioral parameters were assessed through avoidance, elevated plus, and morris water maze. In-vivo studies were conducted by dividing the animals into 4 groups exteroceptive and 5 interoceptive(scopolamine-induced amnesia) 6 animals in each group. The scopolamine was administered at 2mg/kg and the extract of Dragea volubilis was administered at two different doses (100, and 200 mg/kg) for 14 days. Animals were sacrificed after behavioral parameters and brains were isolated for antioxidants and acetylcholinesterase assays. Results: A marked increase in step-down latency (SDL- passive avoidance) and a significant reduction in transfer latency (TL) in the elevated plus maze were noticed with the extract. It also demonstrated significant improvement in memory in the morris water maze (MWM) test in both the training and retention trials. CDV inhibited acetylcholinesterase and reduced thiobarbituric acid reactive substance activity (TBARS) and increased glutathione (GSH) and catalase in the mice brain showing significant antioxidant properties. Conclusion: It can be concluded with results that CDV has significant potential as a nootropic and antioxidant with neuroprotective properties.
Keywords: Antioxidants; CDV; Bacopa monnieri; Dragea volubilis; Alzheimer's disease.